(untitled) (The Pakistan Development Review, 1995)
Water and land development, use, and distribution has played a vital role in agricultural development in Pakistan. The country’s canal irrigation system is the largest contiguous irrigation system in the world-consisting of 40,000 miles of canals and over 80,000 water courses, field channels and ditches running for another million miles [Qureshi and Zakir (1994)]. This irrigation network covers more than 70 percent of Pakistan’s agriculture. Private investment has also contributed significantly to the irrigation system in the form of private tubewells. About 32 percent of farm-gate available water is supplied by the private tubewells, [Government of Pakistan (1988)]. These develoPlIlents have not only brought new land under cultivation but also permitted a considerable increase in cropping intensities.